Rule-Based Approach For Detecting Botnet Based On Domain Name System - Alieyan, Kamal Ibrahim Ahmed (2018)
Botnets are a serious problem in today’s Internet, and they result in economic damage for organizations and individuals. Botnets consist of thousands of infected hosts that receive instructions from command and control (C&C) servers operated by an individual. Traditionally, Internet Relay Chat (IRC) servers are used as C&C servers and communicate with the botnet through IRC channels. As a result, network administrators often block IRC traffic on their networks. Recent trends in botnet development have seen the use of alternative communication channels, such as domain name server (DNS), between the C&C servers and infected hosts (bots).